ENVISIONING SUSTAINABLE LANDSCAPE MANAGEMENT IN THE ENVIRONMENTALLY SENSITIVE AREAS OF KSOUR ESSEF, TUNISIA - Allouche, Faiza Khebour; Hamaideh, Arwa; Hammami, Saida; Gatta, Emna; Khasawneh, Anas (International Journal of Research -GRANTHAALAYAH, 2021)
Each territory has distinctive features and landscape compositions that contribute to the creation of territorial identities. Natural parks are territories remarkable for their wealth of biodiversity, which in turn contribute to the development of sustainable socio-economic development through landscape enhancement. The main idea of this research is to test the combinaison of two concepts to propose a suitable management in a semi-arid environment. It is based on the use of the ESAs and landscape diagnosis concepts. The concept of ESAs is supported including the need to identify environnementally sensitive lands based on the hypotheses of MEDALUS project model. However, the landscape diagnosis is based on the combination of landscape potential and social requirements. Results aimed to create ecological and environmental models based on natural materials such as wood, light minerals and a diversified and multicoloured plant palette, including the logic of working with nature and preserving its particularity by promoting sustainable local development criteria and create a new green city.